An intervention study of Taijiquan on menopausal women's anxiety, depression and muscle strength (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Menopause clinically refers to the pre- and post-menopausal period of women. After women enter menopause, under the dual pressure of gradual deterioration of their physical functions and mental and emotional instability, they are very prone to a variety of physical and mental symptoms. Psychologically they appear as irritability, anxiety, depression and other psychological emotions. Physically they appear as menstruation Stop, insomnia and osteoporosis, etc. According to a survey conducted by the National Health Commission, about 150 million women in my country are undergoing menopause, and more than half of women over 65 suffer from osteoporosis. It is estimated that by 2030, there will be more than 210 million menopausal women in my country. Although female menopause is a normal physiological phenomenon, if it cannot be effectively regulated, it will affect the patient's physical and mental health and quality of life. Therefore, understanding and caring for menopausal women, preventing physical damage caused by osteoporosis and muscle weakness, relieving psychological pressure, and comprehensively improving the physical and mental health of menopausal women is an important topic. Taijiquan is a traditional boxing technique that combines the changes of Yin and Yang and the five elements of the Yi learning, the meridian of Chinese medicine, the ancient Daoyin technique and the vomiting technique. Taijiquan is loose, soft, round, smooth, and effortless. It can dredge the meridians and adjust the balance of yin and yang, which is in line with the physical and mental characteristics of menopausal women. It can eliminate its original clumsiness and stiffness, avoid the damage of muscles, joints, ligaments and other organs; it can also achieve the effect of osteoporosis rehabilitation and relieve psychological pressure. For women who are in menopause, Tai Chi exercise is used as an intervention method to adjust the balance of yin and yang of menopausal women, which can improve the quality of life and happiness index of menopausal women. At the same time, it also provides a valuable theoretical reference for the comprehensive response to the national fitness program policy and the promotion and popularization of Tai Chi. Methods: In order to avoid the "Hawthorne effect" from affecting the accuracy of the experimental results, the experiment adopted a single-blind experiment, concealing the purpose of the experiment from the subjects in order to control the subject's estimated or expected influence on the experimental results. Because menopausal syndrome occurs mostly between 45-60 years of age. The test subjects selected in this article are 42 healthy menopausal women aged 45-60 years with no history of exercise. Participants were randomly divided into experimental group and control group for pre-test. Through single factor analysis, the self-rating anxiety and depression scale and muscle strength test results of experimental group and control group without Tai Chi exercise intervention were compared. There is no significant statistical difference between them to be compared. The experimental group, namely Taijiquan (n=21), practiced 4 times a week, 60min each time, for a total of 6 months of Taijiquan practice (the first 3 months are the basic movement learning stage, the last 3 months are the intensive practice stage). The experimental group practiced 48-style Taijiquan. Among the Taijiquan methods, the focus was on standing stakes and silk-wrapping exercises. Teaching CDs and password guide CDs were distributed and the existing Taijiquan principles were learned and used at the same time. The control group (n=21) maintained their past life habits and only performed general physical exercises. After 6 months of Tai Chi exercise intervention, the experimental group and the control group took the post-test at the same time and received the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) test and muscle strength test. This article uses the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) for menopausal women psychologically. The scale contains 20 items, each with a score of 1 to 4 points. The higher the score, the greater the degree of anxiety or depression. The more serious. Both groups of patients were analyzed by incorporating the data into the SPSS 22. 0 software. The measurement data were compared by t test and expressed as (±s); the count data was by c2 test and expressed as (%), and P<0. 05 indicated that the difference was statistically significant. Learn meaning. Physiologically, muscle strength tests include: upper limb hand grip strength and lower limb quadriceps muscle strength non-conventional body muscle strength physiological testing. Results: After 6 months of Tai Chi exercise prescription intervention, the two groups were psychologically. Before the experiment, the standard scores of anxiety and depression of the experimental group and the control group were basically at the same level. After the experiment, the standard scores of anxiety and depression of the experimental group Significantly lower than the control group, there is a very significant difference (P<0. 001), the experimental group is no anxiety, while the control group subjects still have anxiety; the test within the group shows that the experimental group has passed the intervention of Taijiquan. The degree of anxiety improvement was significantly higher than that of the control group. On the whole, the overall menopausal symptoms, insomnia, dreaminess, irritability, and other menopausal symptoms of the experimental group participating in Tai Chi exercises, as well as their anxiety, have all been effectively and significantly improved. In terms of physiology, the grip strength of the upper limbs of the experimental group increased significantly from 22. 0±4. 1Kgf-1 before exercise to 22. 8±4. 3Kgf- (p=0. 003): but there was no significant difference in the control group without Tai Chi exercises. In the non-dominant leg quadriceps muscle strength test, it was found that the muscle strength of the experimental group and the control group increased significantly (p<0. 05). In the bending down test, it was found that the lowest touch point of the experimental group increased from 0. 6±8. 3 cm above the ground to 3. 3±9. 0 cm below the ground (p<0. 001), but no significant difference was found in the control group. Tests within the group showed that the experimental group's muscle strength was significantly higher than that of the control group after intervention by Tai Chi exercise, and the stretchability of the muscles was increased, which is beneficial to prevent osteoporosis, improve exercise capacity and delay aging. Conclusion: Experiments have proved that Tai Chi is not a single physical or psychological exercise, but an overall exercise of physical and mental coordination. It has a significant effect on alleviating the symptoms of anxiety, depression and insomnia in menopausal women and improving the muscle strength of menopausal women and preventing osteoporosis.